2019
DOI: 10.1111/sode.12419
|View full text |Cite
|
Sign up to set email alerts
|

Gender similarity in growth patterns of support toward friends during young adulthood

Abstract: The purpose of this article was to analyze change over time in a specific aspect of prosocial behavior, emotional support toward friends, using two different methodologies. We examined how emotional support changes during the transition to adulthood and whether gender‐based group comparisons yield different gender patterns than person‐centered growth mixture models. We hypothesized that emotional helping toward friends would increase over time and that person‐centered analyses would not show gender differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It would be advisable to repeat future studies on a larger sample. Secondly, samples should also aim to be more culturally and economically diverse, as well as incorporate diverse measures of gender fluidity such as self‐perceived gender identity and gender‐role orientation (Nielson, Xiao, & Padilla‐Walker, 2019). Importantly, recent studies have shown more symptoms of autism in gender identity disorders such as gender dysphoria (e.g., Janssen, Huang, & Duncan, 2016; van der Miesen, de Vries, Steensma, & Hartman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It would be advisable to repeat future studies on a larger sample. Secondly, samples should also aim to be more culturally and economically diverse, as well as incorporate diverse measures of gender fluidity such as self‐perceived gender identity and gender‐role orientation (Nielson, Xiao, & Padilla‐Walker, 2019). Importantly, recent studies have shown more symptoms of autism in gender identity disorders such as gender dysphoria (e.g., Janssen, Huang, & Duncan, 2016; van der Miesen, de Vries, Steensma, & Hartman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies on best friendship quality during emerging adulthood have revealed a decline in negative features such as antagonism and conflict (Birditt et al, 2009;Yu et al, 2014), an increase in intimacy, and stability when a general positive dimension of quality was examined (Reis et al, 1993;Yu et al, 2014). Other studies on change in quality of friendships in general also found a decrease in conflict and stability or an increase in instrumental or emotional support (Galambos et al, 2018;Nielson et al, 2020;Parker et al, 2012;Pettit et al, 2011).…”
Section: Change In Best Friendship Quality During Emerging Adulthoodmentioning
confidence: 99%
“…Given the limitations of the present study (e.g., correlational design, lack of general language or cognitive measure, focus on the self-report, ethnically homogeneous sample), interpretations of the present findings should be made with caution. Furthermore, paper-and-pencil tasks and self-reports are unlikely to capture such a dynamic and complex process of the development of social cognition and social preferences and require more gender-specific measures (Nielson et al, 2019). Future studies could provide more explicit training for teachers and parents to model and incorporate compassionate and mindful talk into their conversations and private speech, and to look for behaviours that suggest anxious solitude in their students and children respectively.…”
Section: Implications and Future Directionsmentioning
confidence: 99%